The Quest for EEG Power Band Correlation with ICA Derived fMRI Resting State Networks - Meyer, Matthias C.; Janssen, Ronald J.; van Oort, Erik S.; Beckmann, Christian F.; Barth, Markus (Frontiers in Human Neuroscience, 2013)
The neuronal underpinnings of blood oxygen level dependent (BOLD) functional magnetic resonance imaging (fMRI) resting state networks (RSNs) are still unclear. To investigate the underlying mechanisms, specifically the relation to the electrophysiological signal, we used simultaneous recordings of electroencephalography (EEG) and fMRI during eyes open resting state (RS). Earlier studies using the EEG signal as independent variable show inconclusive results possibly due to variability in the temporal correlations between RSNs and power in the low EEG frequency band, as recently reported (Goncalves et al. 2006 and 2008, Meyer et al. (2013)). In this study we use three different methods, including one that uses RSN timelines as independent variable, to explore the temporal relationship of RSNs and EEG frequency power in eyes open RS in detail. The results of these three distinct analysis approaches support the hypothesis that the correlation between low EEG frequency power and BOLD RSNs is instable over time, at least in eyes open RS.